Apakah Pengungkapan ESG Penting Bagi Investor? - Saripah, Dedek; Diantimala, Yossi; Arfan, Muhammad (Universitas Muhammadiyah Malang, 2024)
Purpose: This study examines the significance of ESG disclosure for investors as reflected in the company value of Sharia companies listed on the IDX. Methodology/approach: This study analyses listed Sharia companies’ ESG index on the IDX from 2020 to 2022 with a study sample including 146 observations. A multiple linear regression approach is employed to test the hypothesis. Findings: The results show that environmental disclosure does not affect firm value, while the social disclosure aspect shows a significant positive effect. However, the interesting part is that governance disclosure negatively and significantly affects firm value. Practical implications: Sharia companies need to increase their report on social aspects to gain investor support, while it is necessary to be careful in increasing governance disclosure. Companies must pay attention to their financial structures, they must comply with Sharia principles and not decrease the firm value. Originality/value: This study was conducted to bridge the research gap in previous literature regarding the relationship between partial ESG factors and the value of Sharia companies in Indonesia.